2020
DOI: 10.3390/ijerph17166009
|View full text |Cite
|
Sign up to set email alerts
|

The Needs and Utilization of Long-Term Care Service Resources by Dementia Family Caregivers and the Affecting Factors

Abstract: This study was to evaluate the utilization of long-term care service resources by caregivers of patients with dementia (PWD) and to determine affecting factors. In this cross-sectional study, a total of 100 dyads were enrolled and caregivers responded to the questionnaires. We found 40% of caregivers not using any care resources. Between those caregivers using and not-using care resources, we found differences (p < 0.05) in their health status and living conditions; the difference (p < 0.05) was also fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 34 publications
6
24
0
Order By: Relevance
“…We also found that acculturation was positively correlated with respite care knowledge. In particular, the language component of acculturation may have a notable effect on respite care knowledge; lower language proficiency could become a barrier as a core challenge that makes it difficult for immigrants to navigate the system and acquire information in the new country [8]. The availability of trained interpreters from migrant communities could be one of key aspects for providing migrant-sensitive care [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that acculturation was positively correlated with respite care knowledge. In particular, the language component of acculturation may have a notable effect on respite care knowledge; lower language proficiency could become a barrier as a core challenge that makes it difficult for immigrants to navigate the system and acquire information in the new country [8]. The availability of trained interpreters from migrant communities could be one of key aspects for providing migrant-sensitive care [10].…”
Section: Discussionmentioning
confidence: 99%
“…If caregivers know what the respite care is and understand their variety of forms, they are better able to make effective use of respite care services [7]. However, past studies have shown that 40% of caregivers do not use respite care service resources [8]. Therefore, given the substantial effect of resources on care recipients' outcomes, understanding the meaningful component of these resources is vital, especially regarding respite care knowledge [9].…”
Section: Introductionmentioning
confidence: 99%
“…In Taiwan, old age, cognitive impairment, and functional disabilities are predictors of LTC service use 11 . Dementia care may be distinct from elderly care and care for people with disabilities 12 ; furthermore, most relevant studies have focused on older people receiving either home/community or institutional care, and few studies have investigated the simultaneous use of home/community and institutional care by PWD–caregiver dyads 11,13–15 . Chang et al.…”
Section: Introductionmentioning
confidence: 99%
“…recruited 100 PWD-caregiver dyads from outpatient departments in central Taiwan; the NPSs of the PWDs, the caregivers' health status, and whether the caregivers lived with the PWDs affected the use of LTC resources 14. However, they did not specify what LTC services the PWDs received.…”
mentioning
confidence: 99%
“…Since China has the largest share of global manufacturing output, lower labor force participation due to caregiving could have detrimental long-term effects on the global supply chain. Consequently, providing adequate support for caregivers is likely to reduce the negative impact of a growing dementia population will have on care provision, caregiver well-being, and productivity (Chang et al, 2020; Clay et al, 2019; Amjad et al, 2018). Understanding whether and to what extent families coping with dementia have their needs met is important for clinicians, researchers, and policymakers because unmet needs negatively affect caregivers’ ability to provide support for aging-in-place among persons living with dementia and contribute to caregiver stress, burnout, and worsened mental health.…”
Section: Introductionmentioning
confidence: 99%